Botulinum neurotoxins A, B, C, E, and F preferentially enter cultured human motor neurons compared to other cultured human neuronal populations. Issue 18 (4th July 2019) - Pellett, Sabine; Tepp, William H.; Johnson, Eric A.
Abstract : Human‐induced pluripotent stem cell (hiPSC)‐derived neurons can be exquisitely sensitive to botulinum neurotoxins (BoNTs), exceeding sensitivity of the traditionally used mouse bioassay. In this report, four defined hiPSC‐derived neuronal populations including primarily GABAergic, glutamatergic, dopaminergic, and motor neurons were examined for BoNT/A, B, C, D, E, and F sensitivity. The data indicate that sensitivity varies markedly for the BoNTs tested. Motor neurons are significantly more sensitive than other neuron types for all BoNTs except BoNT/D. Examination of SNARE protein levels and BoNT‐specific cell surface protein receptors reveals few differences between the cell types except greater expression levels of the receptor protein SV2C and synapsin‐IIa in motor neurons. This indicates that differential toxicity of BoNTs for motor neurons compared to other neuronal cell types involves multiple mechanisms. Abstract :